(untitled) (International Journal of Food and Nutritional Sciences, 2019)
This research investigates the intricate connection between filmmakers’ educational qualifications and the quality of films in Telugu cinema. Utilizing a qualitative approach, data is gathered from various sources, including online platforms and personal interviews with renowned directors.